Regionsbildung im Schatten des Metropolendiskurses. Das Fallbeispiel der Region Südwestfalen - Balke, Jan; Reimer, Mario (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Since the mid-nineties, debates about spatial policy in Germany have been marked by a dominance of metropolitan discourses. Apparently these discourses are associated with a gradual shift of spatial policy priorities that more and more give up the primary goal of spatial cohesion in favor of a more competitive approach. In the course of the dominant metropolitan discourse especially regions at the edge of and between metropolitan areas are faced with an increasing pressure of regional profiling. With regard to the case study Südwestfalen the paper focuses on region building in the shadow of the metropolitan discourse. With reference to the Foucauldian concept of governmentality processes of region building and the formation of soft spaces are understood as expressions and means of neoliberal governmentality, and their underlying governmental rationalities and technologies are investigated. The empirical analysis reveals how dominant regional-economic rationalities, logics of inter-municipal cooperation and constraints of subsidy policies frame the process of region building on the discursive level. By analysing discourses and practices of regional marketing and measures of infrastructural self-services it is shown exemplary how contingent technologies of regional self-governance help to govern the process of region building on the collective level and simultaneously unfold subjectifying effects by providing patterns of social meaning and action.
Keywords: Region building; Regionalization; Soft spaces; Neoliberal governmentality